The mediation role of self-esteem and hope on the relationship of quality of life and unmet needs of elderly with psychiatric disorders - Mariye Jenabi Ghods; Ladan Fattah Moghaddam; Mohammad Javad Hosseinabadi-Farahani; Mohammad Pourebrahimi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Self-esteem is one of the factors affecting the quality of life. On the other hand, quality of life decreases in people with psychiatric disorders. The aim of the present study was to evaluate the mediating role of self-esteem and hope on the relationship between unmet needs and quality of life of the elderly with psychiatric disorders. MATERIALS AND METHODS: This descriptive-analytical study was performed on 112 chronic psychiatric patients hospitalized in the geriatric ward of (blinded) 2020. Based on the inclusion criteria, a total of 100 samples were entered into the study by census. The World Health Organization (WHO) quality of life questionnaire, Rosenberg Self-Esteem Scale, Snyder Hope Scale, and Camberwell Assessment of Need Short Appraisal Schedule (CANSAS) were used to collect data. The research model was tested using the path analysis technique. Data was analyzed using Statistical Package for the Social Sciences (SPSS) Ver. 26 and LISREL Ver. 2/9. RESULTS: Unmet needs were negatively related to the other three variables of the study, namely, self-esteem, hope, and quality of life. There was a significant relationship between unmet needs and quality of life with a mediating role of self-esteem and hope (P < 0.05). Quality of life was also negatively related to unmet needs and directly related to self-esteem and hope. CONCLUSION: Based on the findings of this study, it is essential that health-care providers consider planning to provide programs to improve self-esteem and hope in order to reduce unmet needs and increase the quality of life.